Development of glibenclamide validation method using UV-Spectrophotometry for solubility test in mesoporous mannitol - Kusumorini, Nindya; Adhyatmika, Adhyatmika; Biruni, Sheria Itqan; Anugrahanti, Sukmarini (Majalah Farmaseutik, 2023)
This study was aimed to develop a validation method for glibenclamide in mesoporous mannitol using UV spectrophotometric method. This method was chosen because it is simple, sensitive, accurate, precise, reproducible and economical. The wavelength of glibenclamide (λ max) was obtained at 229 nm using ethanol and water in a ratio of 1:1. The linearity of glibenclamide was selected at a concentration of 5 - 17.5 µg/mL. Correlation coefficient (r) = 0.9998; intraday RSD < 1%; interday RSD < 2%, recovery 100 - 105%, LOD = 0.32 µg/mL and LOQ = 1.08 µg/mL, and has high sensitivity because the presence of mesoporous mannitol in the solution does not interfere with the reading process of glibenclamide. So it can be concluded that this method has good reproducibility based on the results of linearity, precision, and accuracy of glibenclamide and in accordance with ICH requirements, so this method can be used for routine analysis of glibenclamide compounds in mesoporous mannitol.